1993
DOI: 10.2472/jsms.42.1193
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Microscopic and Macroscopic Surface Fatigue Cracks under Periodic Overstressing in Ti-6Al-4V Alloy.

Abstract: Microscopic and macroscopic surface fatigue crack propagation studies were carried out under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Strong acceleration effects in the growth of microscopically small fatigue cracks (of lengths below 200 μm) in a low‐carbon steel and a high‐carbon steel under periodic OL blocks ( N OL = 2–100) separated by 2.2 × 10 5 cycles below threshold were also reported in Ref. [135]. Fractographic analyses showed that crack growth increments during the OL blocks were larger than under CA loading at the OL level.…”
Section: Crack Closure In Plane Strain Conditionssupporting
confidence: 61%
See 1 more Smart Citation
“…Strong acceleration effects in the growth of microscopically small fatigue cracks (of lengths below 200 μm) in a low‐carbon steel and a high‐carbon steel under periodic OL blocks ( N OL = 2–100) separated by 2.2 × 10 5 cycles below threshold were also reported in Ref. [135]. Fractographic analyses showed that crack growth increments during the OL blocks were larger than under CA loading at the OL level.…”
Section: Crack Closure In Plane Strain Conditionssupporting
confidence: 61%
“…Hence, it was concluded in Ref. [135] that the acceleration effect was not likely to be related to the crack closure behaviour.…”
Section: Crack Closure In Plane Strain Conditionsmentioning
confidence: 99%
“…In this case, a better correlation was obtained in terms of the effective stress intensity range taking account of the crack closure. ( 5 ) No difference was recognized in the fracture surface morphology between the cases of different mean stress in accordance with the little difference found in crack growth acceleration.…”
Section: (4)mentioning
confidence: 74%